Knowledge Adolescent Girls About Vaginal Discharge - Luna Widiarti; Dewi Rachmawati; Imam Sunarno (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2023)
Vaginal discharge is a reproductive health problem that occurs in most adolescence girls at school. Adolescence girls don't know that if they experience vaginal discharge, the symptoms heal on their own and are not a serious condition. The aim is to find out the knowledge of adolescence girls about vaginal discharge at SMPN 1 Wates. The design uses descriptive with a sample of 30 respondents, the inclusion criteria are adolescence gils aged 12-14 years who have their first menstruation and have vaginal discharge problems. The sampling technique was purposive sampling with questionnaire data collection instruments. Data was taken at SMPN 1 Wates in January-February 2021. The results showed that the knowledge of adolescent girls about vaginal discharge was in the good category as much as 77.5%, in the sufficient category as much as 16.5% and in the poor category as much as 6.2%. It is hoped that health workers will routinely provide health education and youth will actively increase their knowledge through various available media. Keywords: vaginal discharge; knowledge; adolescent girlsPengetahuan Remaja Putri Tentang KeputihanABSTRAK Keputihan menjadi salah satu masalah kesehatan reproduksi yang terjadi pada sebagian besar siswi remaja disekolah. Siswi remaja tidak tahu kalau mengalami keputihan, gejalanya sembuh sendiri dan bukan kondisi serius. Tujuan mengetahui pengetahuan remaja putri tentang keputihan di SMPN 1 Wates. Desain menggunakan deskriptif dengan sampel 30 responden, kriteria inklusi remaja putri usia 12-14 tahun yang pertama kali mestruasi dan mempunyai masalah keputihan. Teknik pengambilan sampel purposive sampling dengan instrumen pengumpulan data lembar kuesioner. Data diambil di SMPN 1 Wates bulan Januari-Februari 2021. Hasil menunjukkan pengetahuan remaja putri tentang keputihan kategori baik sebanyak 77,5%, kategori cukup sebanyak 16,5% dan kategori kurang 6,2%. Diharapkan tenaga kesehatan secara rutin memberikan pendidikan kesehatan dan remaja aktif meningkatkan wawasan melalui berbagai media yang tersedia. Kata kunci: keputihan; pengetahuan; remaja putri